Analisis Perbaikan Proses Bisnis Layanan Handling Garbage Disposal PT. Multi Artha Segoro Menggunakan Pendekatan Lean Six Sigma - Asniar Tirtarani (Fakultas Ilmu Komputer, 2025)
PT. Multi Artha Segoro is a company engaged in providing garbage disposal handling services at Tanjung Emas Port, Semarang. The problem that occurred was a clash due to poor coordination during implementation, so a study entitled "Business Process Improvement Analysis of PT. Multi Artha Segoro’s Handling garbage disposal services by Using the Lean Six Sigma Approach" was needed in order to increase PT. MAS’s performance. Improvements were made using Lean Six Sigma (DMAIC). At the define stage, seven BPMN modeling of the as-is business process of PT MAS HGDS services, SIPOC diagrams, and 10 wastes were produced. The measure stage produces the average time and percentage of resource utilization of the as-is business process whose efficiency will be improved through redesign. At the analyze stage, three root problems are identified through five whys analysis. The improvement stage produces improvement actions through 5W + 1H brainstorming, such as improving the waste collection flow, reaffirming the MoU with partners and creating a supporting service monitoring information system, which is implemented into the redesign of the to be process. The results of the to be process’ performance measurement show a significant increase in efficiency in terms of time, resource, and utilization. The control stage produces a visual design framework for a service support monitoring information system. The results of the improvements show an increase in efficiency in time and resource utilization due to the redistribution of workloads with automation through the system.
Entry oleh Arif 2026 April 01
Keywords: Business Process; Lean Six Sigma; DMAIC